2019
DOI: 10.1093/eurheartj/ehz394
|View full text |Cite
|
Sign up to set email alerts
|

Implications of N-terminal pro-B-type natriuretic peptide in patients with three-vessel disease

Abstract: Aims Risk assessment and treatment stratification for three-vessel disease (3VD) remain challenging. N-terminal pro-B-type natriuretic peptide (NT-proBNP) is an established biomarker for prognostication and treatment in heart failure. The present study aimed to evaluate the prognostic value of NT-proBNP beyond the SYNTAX score II (SSII), and its association with long-term outcome after three strategies [percutaneous coronary intervention (PCI), coronary artery bypass grafting (CABG), and medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 24 publications
2
37
0
1
Order By: Relevance
“…NT-pro-BNP was measured using a commercial sandwich enzyme immunoassay as described previously 15 at hospital admission before the procedure. Other biochemical indicators, including serum blood lipid profiles, blood glucose, Cr, urea nitrogen, uric acid, and levels of electrolytes, were measured as a part of standard clinical care.…”
Section: Detection Of Nt-pro-bnp and Other Biochemical Indicatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…NT-pro-BNP was measured using a commercial sandwich enzyme immunoassay as described previously 15 at hospital admission before the procedure. Other biochemical indicators, including serum blood lipid profiles, blood glucose, Cr, urea nitrogen, uric acid, and levels of electrolytes, were measured as a part of standard clinical care.…”
Section: Detection Of Nt-pro-bnp and Other Biochemical Indicatorsmentioning
confidence: 99%
“…12 In addition, N-terminal pro-B-type natriuretic peptide (NT-proBNP), which is synthesized in cardiomyocytes and released into the circulation, was reported to be a potential biomarker for risk stratification in both ACS patients 13,14 and patients with three-vessel disease. 15 In addition, NT-proBNP can improve the discrimination and reclassification of the C-ACS risk score in ACS patients 16 and of the SYNTAX score II for mortality prediction in patients with three-vessel disease. 15 Therefore, whether a novel prediction model developed using important biomarkers will be more effective needs to be explored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…B-type natriuretic peptide (BNP) or N-terminal pro-BNP (NT-proBNP) may be useful for the diagnosis and evaluation of the severity of heart failure in the setting of ACS [14,15]. Systematic assessment of other biomarkers, such as C-reactive protein or copeptin, though associated with outcomes following ACS, is no longer recommended as their prognosis value compared to BNP/NT-proBNP or the Global registry of Acute Coronary Events (GRACE) score remains limited [16][17][18].…”
Section: Other Biomarkersmentioning
confidence: 99%
“…Study from Berin R et al also displayed that serum NT-proBNP was the strongest predictor of long-term mortality in patients with chronic HF (HR 3.76, 95% Cl, 1.20-11.80; P = 0.008) 20 . In addition, higher NT-proBNP levels were strongly associated with increased risks of all-cause death, cardiac death, and MACCE (P < 0.01) in CAD patients with three-vessel disease 21 and has been considered as a useful biomarker for risk strati cation and therapeutic decision-making. The present study found that there was a wide range of NT-proBNP values in the ACS patients undergoing successful PCI and with LVEF ≥ 50%.…”
Section: Prediction Of Maccementioning
confidence: 99%